Software prototyping for hospitalized patient participation in the medication system (Revista Contexto & Saúde, 2025)
Objective: to develop a prototype to support hospitalized patients' participation in the medication system. Method: this is a methodological study, carried out between March and December 2019, in Fortaleza, Brazil. The study stages were: analysis, design, development, evaluation, and administration. In the first three stages, in addition to the researcher, graphic designers and software programmers participated in organizing the content and navigation architecture. In the following stages, 25 experts (physicians, nurses, and pharmacists) participated in evaluating the software in a simulated environment. The data related to the evaluation were analyzed using the percentage of agreement and the content validity index. Results: the MedPAd software had its operating architecture structured in three integrated devices: web service system (for including prescription and medication dispensing data); server (for programming and data storage); and application (intended for use by the patients, with information about their medication therapy). The experts evaluated functionality, reliability, usability, communicability, applicability and efficiency with an overall agreement percentage greater than 90% and an overall content validity index of 0.94. Conclusion: the prototype presented evidence of validity regarding the tested items.
Keywords: Patient participation; Patient safety; Medication systems in the hospital; Technology